'Wiring' The Wire: Transtextual layers and tragic realism in The Wire. Issue 3 (1st October 2019) - González, Jesús Ángel
The Wire's (2002–08) creator David Simon has contended that it is neither a 'cop' nor a 'crime show' and has called it a 'visual novel' and associated it with Greek tragedy instead. These associations have been contested by critics like Amanda Ann Klein and Linda Williams, who, while praising The Wire, reject its consideration as a Greek tragedy and propose its analysis as television melodrama. This article deals with the different transtextual layers in The Wire, from its obvious connections with cop shows, police procedurals or the hard-boiled detective novel, to its deeper associations with melodrama, going through the more or less veiled references to Dickens, the Greek tragedy, gangster films, westerns or Edgar Allan Poe. By means of this analysis and by applying Jonathan Franzen's concept of 'tragic realism', I reconsider the show's features and generic affiliation, and engage in the debate initiated by Williams contrasting tragedy and melodrama.